2009
DOI: 10.1134/s1063778809050019
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to estimate the Higgs mass from the CMB power spectrum?

Abstract: General Relativity and Standard Model are considered as a theory of dynamical scale symmetry with definite initial data compatible with the accepted Higgs mechanism. In this theory the Early Universe behaves like a factory of electroweak bosons and Higgs scalars, and it gives a possibility to identify three peaks in the Cosmic Microwave Background power spectrum with the contributions of photonic decays and annihilation processes of primordial Higgs, W , and Z bosons in agreement with the QED coupling constant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The observational fact is that the cubic root of the ratio of the third and the second peak momenta (800/546) 1/3 = 1.136 M Z /M W in the Cosmic Microwave Background power spectrum coincides with the ratio of the Z and W masses in good agreement with the experimentally deˇned value M Z /M W = 1.134. This agreement allows us to interpret theˇrst peak (that is two times greater than the last two in accordance with the evolution equation (4.16) and the Bogoliubov transformation (7.8)) as contribution of the two-photon decay of the Higgs particle with the mass m h = 2(220/546) 1/3 M W = 118 GeV lying just in the region preferred by the results of the Standard Model parametersˇtted from the experimental data of LEP [11]. Note that the vacuum postulate in the form of the Dirac constraint of zero momentum of the local volume element (A.20) (with negative contribution into the energy constraint) forbids the Sakharov-type oscillations associated with the CMB power spectrum in the ΛCDM model [5].…”
Section: Standard Model Of Elementary Particlessupporting
confidence: 57%
See 2 more Smart Citations
“…The observational fact is that the cubic root of the ratio of the third and the second peak momenta (800/546) 1/3 = 1.136 M Z /M W in the Cosmic Microwave Background power spectrum coincides with the ratio of the Z and W masses in good agreement with the experimentally deˇned value M Z /M W = 1.134. This agreement allows us to interpret theˇrst peak (that is two times greater than the last two in accordance with the evolution equation (4.16) and the Bogoliubov transformation (7.8)) as contribution of the two-photon decay of the Higgs particle with the mass m h = 2(220/546) 1/3 M W = 118 GeV lying just in the region preferred by the results of the Standard Model parametersˇtted from the experimental data of LEP [11]. Note that the vacuum postulate in the form of the Dirac constraint of zero momentum of the local volume element (A.20) (with negative contribution into the energy constraint) forbids the Sakharov-type oscillations associated with the CMB power spectrum in the ΛCDM model [5].…”
Section: Standard Model Of Elementary Particlessupporting
confidence: 57%
“…It was shown that there is intensive vacuum creation of gravitons and SM bosons due to their Casimir energies at the Planck epoch in the vacuum background of the Empty Universe. The rough estimation [11] shows us that the considered approach to the GR and SM dilaton evolution can yield the vacuum creation of matter in the Universe in agreement with its present-day energy budget. The Early Universe behaves like a factory of electroweak bosons and Higgs scalars.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In the suggested model, the Planck epoch coincides with the thermalization and the electroweak ones. In this case the CMB power spectrum can be explained by two gamma processes of SM bosons [24], avoiding dynamical dilaton deviations with negative energy by means of the Dirac constraint (18). We have provided a few arguments in favour that the exact evolution of the GR as a theory of spontaneous conformal symmetries breaking is related to the equations for the quantum squeezed oscillator.…”
Section: By Means Of the Spin Connection Coefficients Can Be Obtainmentioning
confidence: 99%